Accessibility Built Environment Indicator For Persons With Disabilities In George Town, Penang - Wazani, Ikhwan Ali (2022)
Persons with disabilities confront several challenges that hinder them from fully exercising their rights, and participating in social, professional and cultural activities in terms of accessing built environments. Compared to those without disabilities, persons with disabilities have less opportunities to engage in activities because of their inaccessibility within social environments. This study provided an overview of the accessibility level and investigated the accessibility challenges that persons with disabilities (persons with disabilities of physical, hearing and vision) face when moving around in external built environment in George Town, Penang. Which was carried out with the intention of improving urban design by using Social Network Theory, may have implications for the management of physical mobility for individuals with disabilities. The mixed-method approach was employed to elicit information from organizations related to persons with disabilities, and to obtain data from a group of persons with disabilities. The interviews were conducted with the Penang Island City Council, Think City Penang, George Town World Heritage Incorporated, Penang Society of Disabled Persons and Caring Rehabilitation Society for persons with disabilities. The questionnaire was conducted with wheelchair users, the walking-impaired persons, the visually-impaired persons, and the hearingimpaired persons in George Town areas.